PELATIHAN PEMBUATAN MIE DENGAN CAMPURAN SERBUK DAUN KELOR (MORINGA OLEIFERA) - Tyas, Yayuk Indah Wahyuning; Yatiningrum, Agung; Lidyana, Novita (Abdi Panca Marga, 2023)
Kelor is a plant that can grow quickly, live long, flower all year round, withstand extreme heat conditionsThis plant comes from the tropics and subtropics of South Asia. This plant is commonly used as food and medicine in Indonesia Community Service Activities carried out from January 7, 2022 to January 9, 2022 at 08.00 to 11.00 WIB at Siti Fatimah's mother's house, Ketapang Village, Kademangan District, Probolinggo City concerning Making Noodles with Moringa Oleifera Mixture of Leaf Powder (Moringa Oleifera) participants in this activity are housewives who want to be entrepreneurial. The results obtained from this activity are to increase the creativity of Moringa leaf processing so that it can be used as a mixture of noodles that can be consumed alone and can also be processed into other meanings whose basic ingredients are noodles, so that it can increase family income and have high nutritional value. The result obtained from this service activity is that the participants' skills in this activity increase their knowledge and skills. The knowledge and skills of trainees increased by more than 75% of the total participants. The more difficult the manufacturing process, the lower the percentage of trainee skills. Keywords: training ; Kelor Leaf Noodles